The Cell Cycle G2/M Block Is an Indicator of Cellular Radiosensitivity - Chang Liu; Jing Nie; Rensheng Wang; Weidong Mao (SAGE Publishing, 2019)
Background: Determination of the radiosensitivity of a specific tumor is essential to its precision tumor radiotherapy, but the measurement of cellular radiosensitivity with a routine colony forming assay is both labor- and time-consuming. An alternative option allowing rapid and precise prediction of radiosensitivity is necessary. Methods: In this study, we exposed 4 in vitro cultured cell lines to various doses of X-rays or carbon ions and then measured their radiosensitivities with a routine colony-forming assay, and monitored the kinetics of cell cycle distribution with routine propidium iodine staining and flow cytometry. Results: Based on the results, we correlated cellular radiosensitivity with a dynamic assay of cell cycle distribution, specifically, the negative correlation of cellular radiosensitivity with the accumulated G2/M arrested cells at 48 hours after exposure. The higher the proportion of accumulated G2/M arrested cells at 48 hours after exposure, the lower the radiosensitivity of the cell line, that is, the higher radioresistance of the cell line. Conclusion: These findings provide an optional application of regular cell cycle analysis for the prediction of tumor radiosensitivity.